Education for the Elderly: A New Educational Dimension for the Learning Society of Thailand - Pipatpen, Montana (The Journal of Behavioral Science, 2017)
This article analyzes 1) the educational ideology, educational operations and the effects on life of the elderly; 2) the conditions leading to a review and a question about education that has never been available for the elderly making them “the other” in society; and 3) the unfolding that shows a process of constructing and looking at education with a new dimension known as “education for the elderly” that creates a learning Thai society based on a thinking framework for education that recognizes human value. The results of the analysis with critiques based on modernistic paradigm reveal that the perceptions of the elderly are only representations of negative views and because the educational ideology focuses on producing human resources valuable for the economic system and it turns the elderly into “the other”. Consequently, the elderly are looked at as disabled persons who no longer need learning or education. As a result, a question about the lack of learning society in which the elderly is the important part arises. Thus, a new dimension of education for the elderly to construct a learning society in Thailand is proposed with the following implications. 1) A review of the myths about education, knowledge does not occur only in school where the age ranges are specified, 2) A change of status and position of the elderly to being co-creators of knowledge who can utilize knowledge to be are self-dependent, and 3) Opening of an area of freedom for the elderly to express the value of self-identity and to contribute to providing others in society with life literacy. In this respect, education for the elderly does not have a fixed meaning as aimed by the state, and it does not refer to any one particular series of knowledge. Rather, it can change according to interaction, criticism, or negotiation to enable people who are made “the other” to remain their existence in society with dignity. Keywords: education, elderly, learning society